Women's Tefillah Groups and the Boundaries of Jewish Orthodoxy - Mayne, Hannah (AJS review, 2022)
This article looks at women's tefillah (prayer) groups (WTGs) as an anthropological case study to consider how an initially radical movement on the margins quickly moved into, and thereby changed, the center of Jewish Modern Orthodoxy. I take up this example in order to reflect on processes of religious transformation, and to think about Orthodoxy as the product of negotiated boundaries between female lay leaders and male rabbinic authorities. Drawing on ethnographic fieldwork, the first section gives an account of a WTG service at an American Modern Orthodox synagogue. The following sections document some of the main concerns that motivated and hampered WTG founders and leaders, largely from their perspectives. I examine their establishment of groups in the face of halakhic and institutional opposition, their practical liturgical strategies, and their negotiation of feminist sensibilities and Orthodox piety. The article then offers some concluding thoughts on Orthodoxy as an analytical and theoretical category.